AN ANALYSIS OF ILLOCUTIONARY ACTS FOUND IN WOLFWALKERS MOVIE - Wayan Sari; I G. A. Vina Widiadnya Putri (PROJECT (Professional Journal of English Education), 2022)
This article entitled An Analysis of Illocutionary Acts Found in Wolfwalkers Movie. This article focuses on identifying utterances that use illocutionary act.There are two problems discussed in this study, those are what types of illocutionary acts found in Wolfwalkers movie and what are the functions of illocutionary acts expressed in Wolfwalkers movie. To answer the problems this article used two theories. First, the theory of types illocutionary acts proposed by Searle (1979) and the second theory from Leech (1983) to analyze the function of illocutionary act. The researcher used descriptive qualitative method to describe the data to answer the problem of the study. The study's findings indicate that there are 47 data of types illocutionary act. Keywords:  Illocutionary Acts, Function, Movie